Utility and Risk Aversion Coefficients in DSGE Models – The Case of the Czech Republic - Vérosta, Denis (2019)
This thesis investigates capabilities of simple real business cycle and new Keynesian models, specified with various utility function types and various values of the relative risk aversion parameter. Models are first solved for utility function of constant relative risk aversion. This serves as a benchmark for more complex utility functions such as habit formation and non-separability between consumption and hours worked. Theoretical moments of models are derived and compared to the HP filtered empirical moments of the Czech economy. It is shown that the best results were obtained for the new Keynesian model with internal habit utility function and low values of RRA = 1 and 2.